STRATEGI PEMASARAN KEMITRAAN PADA SEKOLAH VOKASIONAL SWASTA DI MASA PANDEMI COVID-19 UNTUK MENINGKATKAN PENDAFTARAN PESERTA DIDIK BARU (PPDB) TAHUN AJARAN 2021/2022 - Gresi Alun Meidianto; Ismet Basuki; Sri Setyowati (re-JIEM (Research Journal of Islamic Education Management), 2022)
The Covid-19 pandemic has created intense competition in the world of education and has transformed the focus of education management from a simple way to serve the institutional education process, to a way to transform users of education services (user education) into customer education (customer education). Private educational institutions experienced a decrease in the number of students for the 2021-2022 school year due to the pandemic. The Covid-19 pandemic tested the marketing strategies of every educational institution. Schools that have the opportunity to survive are those that have strategies to create competitive and sustainable advantages. This research uses a qualitative approach with the design of case studies. The subjects of this study consisted of the Principal, Deputy Principal, teachers, administrative staff, parents of students and students. Data collection techniques include documentation studies, field observations and in-depth interviews. In this study to analyze data using Creswell's data analysis model. Partnership marketing strategies are considered the most appropriate to support school targets in acquiring new customers of educational services in the 2021/2022 school year. The school strives to embrace and establish partner relationships with the community as a front liner marketing school education services